Sustainable and Development Energy Resilience in Multidisiplinary Prespective - Harsono, Ony Anwar (RSF Conference Series: Business, Management and Social Sciences, 2023)
Energy is one of the things that greatly affects human life, many operational processes and energy development planning that need to be updated because there have been many problems in the form of delays in energy access to several billion people around the world. In order to achieve succession in SDG's seventh point, namely affordable and clean energy and the thirteenth point, namely climate action, in sustainable energy development, these two points become the main reference for further energy developments to be implemented. Therefore, researchers through this study try to discuss Sustainable and Development Energy Resilience In Multidicpinary Prespective, with the aim of deepening views related to the importance of studying sustainable energy development and security in a multidisciplinary perspective, namely social perspective, economic perspective, and environmental perspective (climate change mitigation). By presenting a literature review of previous studies related to the elements discussed in this study, it is hoped that the objectives and results of this research can provide a fairly good theoretical contribution in sustainable and development energy resilience. The results of this study state that if stakeholders consider energy and refer to Chester (2010) related to the components that need to be considered in energy development, namely availability, accessibility, affordability and community acceptance. So if the four components are maintained and considered properly, then the energy needs of the global community can be met sustainably.